Søren Kierkegaard Educating for Authenticity - Klausen, Søren Harnow (SpringerBriefs on Key Thinkers in Education,, 2018)
This book is a succinct guide to Søren Kierkegaard's contribution to educational thought. Kierkegaard is not usually known as an educational thinker, but the book shows how his key notions and ideas are nevertheless highly relevant to educational theory and practice. It places them within the context of Kierkegaard's philosophy and the philosophy of his time, while also exploring their significance to issues of contemporary concern, like the question of how far education should aim at fostering useful skills or support more ambitious goals. The central topics are Kierkegaard's diagnosis of the limitations of objective knowledge and his corresponding emphasis on know-how, personal appropriation and subjective attitude; his analysis of more or less successful forms of self-realization; his ideas about fostering personal development through "indirect communication" and dialogue; and the elements, strengths and shortcomings of the ideal of self-cultivation (German Bildung). .